Lymphoedema management in podoconiosis - Authors reply - Molla, M; Ngari, M; Berkley, J; Njuguna, P; Fegan, G; Lang, T; Newport, M; Enquoselassie, F; Davey, G; Golbet Team, (Elsevier, 2018)
We thank Jill Brooks and colleagues for their comments on how their trial was referred to in our article.